First Trimester Metabolites Predict Gestational Diabetes Mellitus Diagnosis: A Case: Control Study (FS03-04-19). (13th June 2019) - Ramos, Manuel; Lamb, Anna; Alarcon, Noemi; Quintana-Diaz, Adilene; Fanter, Rob; Phelan, Suzanne; Frano, Michael La
Abstract: Objectives: Gestational Diabetes Mellitus (GDM) has an overall prevalence estimated as high as 13% of overweight/obese (OW/OB) pregnant women. Since the occurrence of GDM can have a combination of adverse perinatal outcomes and long-term increased risk of health issues in the future for both the mother and child, it is important that the mechanisms involved in this disease are better understood so that better prevention strategies can be devised. We sought to identify early and late pregnancy metabolites that discriminated women who developed vs. did not develop GDM to provide insight into its etiology and help improve treatments. Methods: Participants were 26 OW/OB women enrolled in the Healthy Beginnings Trial and completed blood draws at 13 weeks, 26 weeks, and 35 weeks gestation. Participants from the control and dietary intervention group who developed GDM (N = 12) were matched on age and study entry BMI with those who did not develop GDM (N = 14). Plasma samples were analyzed by ultra-high-performance liquid chromatography-hybrid triple‐quadrupole linear ion trap mass spectrometry (UPLC-QTRAP) using two targeted metabolomics assays for primary metabolomics and aminomics. Results: A total of 142 metabolites were identified. Most metabolite differences were observed during the first trimester blood draw, prior to GDM diagnosis. At first trimester, metabolites related to energy metabolism that were altered included lower levels of alpha-ketoglutarate and glycerol-3-phosphate, as well as the medium-chain acylcarnitines' lauroyl-carnitine, dodecenoyl-carnitine, and octanoyl-carnitine ( P < 0.05). Interestingly, the neurotransmitters serotonin and glutamate were elevated in subjects who later developed GDM ( P < 0.01). In regards to the observed elevated creatine, the lower concentrations of methionine and glycine may suggest utilization of these amino acids for its production ( P < 0.03). Lastly, the gut microbiota-derived indole-3-propionate was higher in GDM cases ( P < 0.05). In the third trimester of the GDM group, only levels of 4-pyridoxate (vitamin B-6) were lowered ( P < 0.05). Conclusions: Metabolic changes associated with the numerous plasma metabolites that were different between GDM case-control subjects during first trimester may predict the development of this condition. Funding Sources: NIH, ARI.